Rivalry in the information sphere Russian conceptions of information confrontation - Grisé, Michelle (RAND, National Defense Research Institute, 2022)
Information and information technologies infuse all parts of modern society-in peacetime, during periods of strategic competition, and during wartime. Since the early 2000s, advanced information technologies for rapidly sharing, processing, and analyzing data have had a significant effect on the character of Russian military operations. An examination of the Russian military-scientific literature reveals the centrality of the concept of information confrontation in Russian military strategy. Information confrontation, or informatsionnoe protivoborstvo (IPb), is a distinct element of Russian strategic thinking in the post-Cold War era. Russia sees itself as being in a constant state of information confrontation with the West as it tries to expand its own dominance and prevent its adversaries from gaining influence. In this report, the authors examine prevailing definitions and types of information confrontation, and they discuss the historical evolution of Russian (and Soviet) influence operations and psychological warfare, from 18th-century Imperial Russia up to the Vladimir Putin era. As a fundamental element of Russian strategy, information confrontation is evolving from something primarily carried out to supplement traditional means of waging war into something that is carried out continuously and in peacetime to shape the operational environment so that it will be malleable in future conflicts. The authors also analyze the experience of Ukraine, which has been the subject of one of Russia's most comprehensive IPb and hybrid warfare campaigns in recent years. Ukraine offers a window into the present-day role of IPb and Russian activities and intentions in the information domain.
"Prepared for the U.S. European Command ; approved for public release; distribution unlimited"
Keywords: Geschichte; Psychologische Kriegführung; Information warfare; Russland; Information warfare / Russia (Federation); Psychological warfare / Russia (Federation); Hybrid warfare / Russia (Federation); Russia (Federation) / Foreign relations / Ukraine; Ukraine / Foreign relations / Russia (Federation)